Advances in epigenome-wide association studies for common diseases - Dirk S. Paul; Stephan Beck (2014)
Epigenome-wide association studies (EWASs) provide a systematic approach to uncovering epigenetic variants underlying common diseases. Discoveries have shed light on novel molecular mechanisms of disease and enabled the application of epigenetic variants as biomarkers. Here, we highlight the recent advances in this emerging line of research and discuss key challenges for current and future studies.